2016
DOI: 10.3389/fcimb.2016.00058
|View full text |Cite
|
Sign up to set email alerts
|

Hacker within! Ehrlichia chaffeensis Effector Driven Phagocyte Reprogramming Strategy

Abstract: Ehrlichia chaffeensis is a small, gram negative, obligately intracellular bacterium that preferentially infects mononuclear phagocytes. It is the etiologic agent of human monocytotropic ehrlichiosis (HME), an emerging life-threatening tick-borne zoonosis. Mechanisms by which E. chaffeensis establishes intracellular infection, and avoids host defenses are not well understood, but involve functionally relevant host-pathogen interactions associated with tandem and ankyrin repeat effector proteins. In this review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 143 publications
(224 reference statements)
0
41
0
Order By: Relevance
“…lar trafficking and cytoskeletal organization, and apoptosis (4,5). Most recently, E. chaffeensis via the TRP120 effector was shown to activate Wnt and Notch signaling pathways to promote intracellular survival (6,7).…”
mentioning
confidence: 99%
“…lar trafficking and cytoskeletal organization, and apoptosis (4,5). Most recently, E. chaffeensis via the TRP120 effector was shown to activate Wnt and Notch signaling pathways to promote intracellular survival (6,7).…”
mentioning
confidence: 99%
“…Ankyrin repeats mediate protein–protein interactions, provide scaffolding for signalling pathways and localize molecules to subcellular compartments in eukaryotes 88 . Ankyrin-repeat containing proteins (Anks) in A. phagocytophilum and E. chaffeensis were shown to mediate host epigenetic changes to promote bacterial survival 69,89 . Elucidating the function of conserved Anks in obligate intracellular bacteria can provide insight into host signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A homolog of Erum1110 was previously implicated with attachment to tick cells (De la Fuente et al, 2004). Previous studies have reported that TR-proteins elicit a strong protective antibody response during infection that is directed at continuous species-specific epitopes located at the TR region (Lina et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these genes may possibly be ideal targets for CTL immunity. Lina et al (2016) reviewed that pathogenicity-associated genes (e.g. type IV secretion system proteins (T4SS)) play an important role in the in E. chaffeensis growth and virulence.…”
Section: Discussionmentioning
confidence: 99%